Ankyloblepharon Filiforme Adnatum in a Newborn - Giulia Bordin; Enrico Valerio; Mario Cutrone (Thieme Medical Publishers, Inc., 2015)
Abstract Ankyloblepharon filiforme adnatum (AFA) is a rare congenital anomaly consisting of a partial or complete fusion of the eyelid margins. It is usually an isolated and benign malformation but its presence should alert the neonatologist because it can be rarely associated to other important multisystemic disorders. We report a case of a newborn presenting with isolated AFA at birth, treated in the first day of life.